The university student and synchronous communication devices: Uses, profiles and didactic consequences: El alumno universitario y los dispositivos de comunicación sincrónica: usos, perfiles y costumbres escritoras (Papeles, 2024)
The digitally enveloping society in which we find ourselves bases its actions on communication, especially synchronous, and on the development of new technological devices. The main objective of this study is focused on knowing the digital writing of future teachers, through an orthographic analysis, as well as investigating and assessing behaviors when using instant messaging applications and social communication networks. As future teachers, it is essential and decisive in their profession to display impeccable spelling. Methodology: A quantitative investigation has been carried out, through an analysis based on frequency percentages of writing uses and customs, through the development and application of a questionnaire, to a total of 116 students belonging to the first year of the degree in Early Childhood Education and Primary Education from the Faculty of Education of the University of Extremadura. Results and conclusions: The results show that what they use the least are punctuation marks; however, they no longer substitute letters and correctly use writing in homophonous words.
Keywords: Communication mobile; university student; writing; orthography